Public sector ethics : finding and implementing values - Sampford, C. J. G. (Charles J. G.); Preston, Noel, 1941-; Bois, C.-A. (Carol-Anne), 1960- (Leichhardt, NSW : Federation Press ; London ; New York : Routledge, 1998)
This study, with contributions from both scholars and practitioners, examines the theory and practice of public sector ethics across a broad range of environments.
Book Cover; Title; Contents; About the Contributors; Introduction; Public Sector Ethics: Prospects and Challenges Tom Sherman; Against Professional Ethics Hendrik Kaptein; Authority, Discretion and Accountability: The Case of Policing Seumas Miller; Business Practices and the Public Service Ethos Alan Lawton; Clarifying Accountability: An Ethical Theory Framework Mel Dubnick; Ethics in Public Service: An Idea Whose Time Has Come Stephen D Potts; Corruption in Socialist and Capitalist Countries Young Jong Kim; Integrating Ethics Colin Hicks and Gerald Scanlan.
Includes bibliographical references (pages 163-172) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Civil service ethics; Public administration -- Moral and ethical aspects; Public officers -- Professional ethics; Political ethics; Administrative agencies -- Moral and ethical aspects; Public utilities -- Moral and ethical aspects; Fonctionnaires -- Déontologie.; Administration publique -- Aspect moral; Services publics -- Aspect moral; Administration publique (Science) -- Aspect moral; Morale politique; POLITICAL SCIENCE -- General; Civil service ethics; Political ethics; Public administration -- Moral and ethical aspects; Public officers -- Professional ethics; Beroepsethiek; Ambtenaren; Openbaar bestuur